Plague and Empire in the Early Modern Mediterranean World: The Ottoman Experience, 1347-1600 / Nükhet Varlık - Ozancan Bozkurt (Journal of Universal History Studies, 2022)
Nükhet Varlık, who completed her undergraduate and graduate studies at Boğaziçi University, received her Ph.D. at the University of Chicago in 2008. She currently works as Associate Professor in the History Department at Rutgers University and continues her research on subjects such as medicine, epidemics, and death in the Ottoman Empire. Plague and Empire in the Early Modern Mediterranean World: The Ottoman Experience, 1347–1600 is the first systematic and critical historical study to examine the plague experience of the Ottoman Empire between the late medieval and early modern period within the framework of its political and social dimensions. In addition, the fact that the book was awarded both in Turkey and abroad following the years it was published reveals the impact and the importance of the work